2021
DOI: 10.3389/fcvm.2021.709079
|View full text |Cite
|
Sign up to set email alerts
|

MiR-3064 in Epicardial Adipose-Derived Exosomes Targets Neuronatin to Regulate Adipogenic Differentiation of Epicardial Adipose Stem Cells

Abstract: Backgroud: The metabolism of epicardial adipose tissue (EAT) is closely related to coronary atherosclerotic heart disease (CAHD), but the specific mechanism is not fully understood. In this study, we investigated the effects of EAT microenvironment on adipose metabolism from the viewpoint of EAT-derived exosomes and epicardial adipose stem cells (EASCs).Methods: EAT samples from CAHD patients and non-CAHD patients were collected to obtain exosomes via tissue culture. MiRNA sequencing was performed to analyze d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…PCAT refers to the part of epicardial fat that directly contacts the coronary arteries, facilitating bidirectional conduction between them and playing a crucial role in coronary atherosclerosis. 35 , 36 , 37 PCAT attenuation, as determined by coronary CTA, has been identified as an indicator of coronary inflammation. Our study consistently found that LAD‐PCAT was significant in all adjusted models of multiple linear regression.…”
Section: Discussionmentioning
confidence: 99%
“…PCAT refers to the part of epicardial fat that directly contacts the coronary arteries, facilitating bidirectional conduction between them and playing a crucial role in coronary atherosclerosis. 35 , 36 , 37 PCAT attenuation, as determined by coronary CTA, has been identified as an indicator of coronary inflammation. Our study consistently found that LAD‐PCAT was significant in all adjusted models of multiple linear regression.…”
Section: Discussionmentioning
confidence: 99%
“…Nnat regulates the adipogenic differentiation of preadipocytes, thereby improving adipose tissue metabolism. It is also a therapeutic target for atherosclerosis (Yang et al, 2019(Yang et al, , 2021. Nnat is considered an important regulator of glucose homeostasis and normal lipid metabolism under physiological conditions (Asahara, 2018;Gburcik et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…43 A recent study showed that Nnat regulates the normal fat metabolism of the epicardial adipose tissue. 44 In highfat diet-fed mice, Nnat was proved as a SERCA uncoupler in cells and may function in adaptive thermogenesis. 45 However, the role of Nnat in glycorenal lipid metabolism has not been reported yet.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The deletion of Nnat reduces basal and insulin-stimulated glucose uptake and glycogen synthesis without affecting the insulin signal, and, therefore, it is an important regulator of white adipocyte browning and metabolic substrate treatment . A recent study showed that Nnat regulates the normal fat metabolism of the epicardial adipose tissue . In high-fat diet-fed mice, Nnat was proved as a SERCA uncoupler in cells and may function in adaptive thermogenesis .…”
Section: Discussionmentioning
confidence: 99%